EFFECTS OF PROCESSED FOOD CONSUMPTION ON LEPTIN, GHRELIN, AND THE DEVELOPMENT OF OBESITY (CIPEEX, 2025)
The industrialization of food production profoundly transformed dietary habits, increasing the consumption of ultra-processed products characterized by high palatability, convenience, and low nutritional value. These products, often rich in sugars, fats, and sodium, have been consistently associated with negative metabolic consequences, including alterations in appetite-regulating hormones. Among them, leptin and ghrelin are central to energy homeostasis and weight regulation. Ghrelin, secreted primarily by the stomach, stimulates appetite and promotes feeding behavior during fasting, while leptin, produced mainly by adipocytes, signals satiety to the central nervous system and regulates energy expenditure. This integrative mini-review aimed to analyze the relationship between ultra-processed food consumption and hormonal imbalance involving leptin and ghrelin. A literature search was conducted in September 2025 using PubMed, SciELO, and Google Scholar, applying descriptors in Portuguese, English, and Spanish. Inclusion criteria comprised original studies published between 2020 and 2025, available in full text and open access. From an initial pool of 600 articles, five studies met all inclusion requirements. Results demonstrated that diets rich in ultra-processed foods impair nutritional balance and disrupt hormonal regulation. Leptin resistance emerges as a consequence of increased adiposity, diminishing central sensitivity despite elevated serum levels, which compromises appetite control and energy expenditure. Concurrently, ghrelin, while physiologically essential in promoting hunger, may perpetuate excessive food intake and fat accumulation when chronically elevated. The interplay between both hormones underlines the complexity of obesity development, suggesting that disrupted signaling pathways contribute significantly to weight gain and associated metabolic disorders. Furthermore, the findings reinforce that ultra-processed diets, enriched with refined carbohydrates, fats, and sodium but lacking in essential micronutrients, create favorable conditions for hormonal dysregulation, metabolic imbalance, and chronic disease progression. From a public health perspective, these insights highlight the urgent need for policies addressing nutritional education, regulation of processed food availability, and promotion of healthier dietary patterns. Educational campaigns and preventive strategies may reduce population-level exposure to harmful food environments, while clinical interventions should target the identification of hormonal alterations in high-risk individuals. For researchers, the topic remains underexplored, particularly regarding ghrelin’s long-term role in metabolic adaptation, genetic predisposition, and interaction with diverse dietary patterns. Understanding these mechanisms could support innovative therapeutic approaches to obesity management and prevention. In conclusion, excessive consumption of ultra-processed foods is directly associated with leptin and ghrelin imbalance, which compromises appetite regulation, fosters energy storage, and contributes to obesity and related metabolic diseases. Addressing this problem requires an integrative strategy combining scientific research, public policy, and clinical practice to mitigate the harmful impact of dietary industrialization and to promote healthier lifestyles across populations.
Keywords: Grelina; Leptina; Obesity; Processed Foods